Correction: Computational investigation of the increased virulence and pathogenesis of SARS-CoV-2 lineage B.1.1.7. Issue 42 (25th October 2022) - Murugan, N. Arul; Javali, Prashanth S.; Pandianb, Chitra Jeyaraj; Ali, Muhammad Akhtar; Srivastava, Vaibhav; Jeyaraman, Jeyakanthan
Abstract : Correction for 'Computational investigation of the increased virulence and pathogenesis of SARS-CoV-2 lineage B.1.1.7' by N. Arul Murugan et al., Phys. Chem. Chem. Phys., 2022, 24, 20371–20380, ; https://doi.org/10.1039/D2CP00469K .